EVALUASI KONDISI ANGKUTAN MASAL DI JABODETABEK AKIBAT PSBB - Lensi Oktavia Stini (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2020)
Jabodetabek development has had an impact on the supporting transportation system, the more developed Jabodetabek, the more developed the existing transportation system. But at this time in various countries in the world there is an outbreak of Covid-19 which has a major impact on all aspects. In Indonesia a system has been set up aimed at suppressing the expansion of the Covid-19 outbreak by implementing a Large-Scale Social Restrictions (PSBB) system. Large-scale social restrictions are restrictions on certain activities of residents in an area suspected of being infected with Corona Virus Disease 2019 (COVID-191 in such a way as to prevent the possibility of spreading Corona Virus Disease 2019 (COVID-I9). Large-scale Social Restrictions must be based on epidemiological considerations, the magnitude threats, effectiveness, support of resources, operational technical, political, economic, social, cultural, defense and security considerations.The impact of the PSBB is strongly felt in aspects of the existing transportation system, therefore there is a need to study